2007
DOI: 10.1111/j.1742-4658.2007.05848.x
|View full text |Cite
|
Sign up to set email alerts
|

Acidic extracellular pH increases calcium influx‐triggered phospholipase D activity along with acidic sphingomyelinase activation to induce matrix metalloproteinase‐9 expression in mouse metastatic melanoma

Abstract: Acidic extracellular pH is a common feature of tumor tissues. We have reported that culturing cells at acidic pH (5.4-6.5) induced matrix metalloproteinase-9 expression through phospholipase D, extracellular signal regulated kinase 1 ⁄ 2 and p38 mitogen-activated protein kinases and nuclear factor-jB. Here, we show that acidic extracellular pH signaling involves both pathways of phospholipase D triggered by Ca 2+ influx and acidic sphingomyelinase in mouse B16 melanoma cells. We found that BAPTA-AM [1,2-bis(2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 54 publications
1
85
0
1
Order By: Relevance
“…7 This leads to normal cell death via caspase-mediated activation of p53-dependent apoptotic pathway, 8,17 whereas cancer cells are well equipped to export lactate by MCTs transporters resulting in the acidification of microenvironment. 18 A low pH created by extracellular acidification provides a favorable microenvironment for the activation of proteases, including MMPs, 19 urokinasetype plasminogen activator, 20 25 Therefore, tumor cells become migratory and invasive because they disturb the environment so that it is optimal for their proliferation and toxic to the normal cells with which they compete for space and substrate.…”
Section: How Does the Glycolysis Pathway Affect Tumor Cell Migration mentioning
confidence: 99%
See 1 more Smart Citation
“…7 This leads to normal cell death via caspase-mediated activation of p53-dependent apoptotic pathway, 8,17 whereas cancer cells are well equipped to export lactate by MCTs transporters resulting in the acidification of microenvironment. 18 A low pH created by extracellular acidification provides a favorable microenvironment for the activation of proteases, including MMPs, 19 urokinasetype plasminogen activator, 20 25 Therefore, tumor cells become migratory and invasive because they disturb the environment so that it is optimal for their proliferation and toxic to the normal cells with which they compete for space and substrate.…”
Section: How Does the Glycolysis Pathway Affect Tumor Cell Migration mentioning
confidence: 99%
“…108 High lactate concentration could induce the necrosis and apoptosis of normal tissues and release of cathepsin B and other proteolytic enzymes, which results in the degradation of extracellular matrix and initiates cancer cell migration. [19][20][21][22][23][24] It is reported that metastasis of tumors is promoted by lactate-induced secretion of hyaluronan that creates a milieu favorable for migration. 109 Intriguingly, lactate itself has been found to induce the migration of cancer cells.…”
Section: How Does Pentose Phosphate Pathway Affectmentioning
confidence: 99%
“…Finally, the activity of matrix metalloproteinases has also been linked to Ca 2þ signalling [105,106]. The upregulation of MMP9 requiring Ca 2þ influx can therefore be inhibited by blocking voltage-gated Ca 2þ channels [107].…”
Section: Ionic Mechanisms Of Tumour Cell Invasionmentioning
confidence: 99%
“…3C, top). Furthermore, because the expression of L-type calcium channels was reported in melanoma cells (20), we examined the effect of inhibition of these calcium channels on Epac-induced Ca 2+ signal. Neither verapamil nor nifedipine, L-type Ca 2+ channel blockers, inhibited Epac-induced Ca 2+ signal (Fig.…”
Section: Epac Increases Intracellular Camentioning
confidence: 99%